2016
DOI: 10.1021/acs.nanolett.6b01311
|View full text |Cite
|
Sign up to set email alerts
|

Disparate Strain Dependent Thermal Conductivity of Two-dimensional Penta-Structures

Abstract: Two-dimensional (2D) carbon allotrope called penta-graphene was recently proposed from first-principles calculations and various similar penta-structures emerged. Despite significant effort having been dedicated to electronic structures and mechanical properties, little research has been focused on thermal transport in penta-structures. Motivated by this, we performed a comparative study of thermal transport properties of three representative pentagonal structures, namely penta-graphene, penta-SiC2, and penta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
143
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(155 citation statements)
references
References 54 publications
11
143
1
Order By: Relevance
“…However, the out-of-plane acoustic modes are still marked with ZA modes. It is clearly seen that LA and TA branches are linear near the Γ point, while ZA branch deviates from linearity, which shares the general feature of 2D materials [8][9][10][11][12][13][14][15][16][17][18][19][20] . It is clearly seen that both acoustic and optical branches overall move downward from As to SbAs to Sb monolayer, and the widthes of acoustic and optical branches gradually become narrow.…”
Section: Main Calculated Results and Analysismentioning
confidence: 89%
“…However, the out-of-plane acoustic modes are still marked with ZA modes. It is clearly seen that LA and TA branches are linear near the Γ point, while ZA branch deviates from linearity, which shares the general feature of 2D materials [8][9][10][11][12][13][14][15][16][17][18][19][20] . It is clearly seen that both acoustic and optical branches overall move downward from As to SbAs to Sb monolayer, and the widthes of acoustic and optical branches gradually become narrow.…”
Section: Main Calculated Results and Analysismentioning
confidence: 89%
“…40 It is reported that the large contribution of the ZA mode to the κl of graphene is due to a symmetry selection rule which strongly restricts anharmonic phonon-phonon scattering of the ZA mode, resulting in much larger relaxation time of ZA mode compared to the in-plane acoustic branches. 39 However, the out-of-plane symmetry is broken in puckered structure such as phosphorene 46 , arsenene, 49 even pentagonal graphene, 50 where the symmetry-based phonon-phonon scattering selection rule doesn't work, leading to a larger scattering rate and shorter relaxation time of the ZA mode. As a result, the contribution of ZA mode in borohane, which is a 2D material of puckered structure, should be less than graphene.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that, from S atom to Te atom (also from C atom to Pb atom), the atomic radius becomes larger in the order of S < Se < Te (C < Si < Ge < Sn < Pb), thus the lattice constants and bond lengths should be increased correspondingly. As shown in the top view, one can see those 2D p-IVX 2 crystals are akin to the structure of experimentally identified pentagraphene and are composed completely of the pentagonal rings [46][47][48]. The summary of the topological states of the full 15 different p-IVX 2 based on HSE06 method is given in Fig.…”
Section: Resultsmentioning
confidence: 89%